2018
DOI: 10.1111/rego.12232
|View full text |Cite
|
Sign up to set email alerts
|

Policing alienated minorities in divided cities

Abstract: Minority groups frequently challenge the legitimacy of legal authorities, particularly the police. Without trust and legitimacy, the police encounter constant conflict and cannot function effectively. While past research has examined minorities’ perceptions of the police, national minorities provide an interesting and under‐investigated test case because of their inherent identity conflict with the state. The current research examines three factors to explain minority–majority disparities in views of the polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…A majority of studies using this approach have found that the most important predictor of legitimacy is the extent to which people think that officers act in procedurally just ways-more important than for example perceptions of the effectiveness of the police in reducing crime and responding to victims. This is the case in the USA (Sunshine and Tyler 2003;Reisig et al 2007;White et al 2016), UK (Huq et al 2011;Bradford 2014), Australia (Murphy and Cherney 2012;Murphy et al 2016Murphy et al , 2018, Israel (Mentovich et al 2018), China (Sun et al 2017) and Continental Europe (Hough et al 2013a(Hough et al , 2013b; Dirikx and Van den Bulck 2013). Procedurally just police conduct seems to act as a legitimating process of justification, while procedurally unjust police conduct seems to act as a delegitimating process of contestation (Tyler 2017).…”
Section: The Standard Approach To Studying Empirical Legitimacymentioning
confidence: 99%
“…A majority of studies using this approach have found that the most important predictor of legitimacy is the extent to which people think that officers act in procedurally just ways-more important than for example perceptions of the effectiveness of the police in reducing crime and responding to victims. This is the case in the USA (Sunshine and Tyler 2003;Reisig et al 2007;White et al 2016), UK (Huq et al 2011;Bradford 2014), Australia (Murphy and Cherney 2012;Murphy et al 2016Murphy et al , 2018, Israel (Mentovich et al 2018), China (Sun et al 2017) and Continental Europe (Hough et al 2013a(Hough et al , 2013b; Dirikx and Van den Bulck 2013). Procedurally just police conduct seems to act as a legitimating process of justification, while procedurally unjust police conduct seems to act as a delegitimating process of contestation (Tyler 2017).…”
Section: The Standard Approach To Studying Empirical Legitimacymentioning
confidence: 99%
“…Crucially, police effectiveness and whether police allocate outcomes such as arrests, citations, protection, and service fairly across aggregate social groups (i.e. distributive justice) are typically less important predictors of legitimacy in these contexts (Tyler, 2006a;Mazerolle et al, 2013;Bradford et al, 2014a;White et al, 2016;Mentovich et al, 2018). 2 Legitimacy has also been shown to be more important predictor of legal compliance than instrumental factors based on deterrence and fear of sanction (Tyler, 2006a(Tyler, , 2006bPapachristos et al, 2012;Jackson et al, 2012;Murphy et al, 2016;Trinkner et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…What might the context of Sao Paulo, Brazil, mean for the construal of legitimacy, its antecedents, and its consequents? By way of contribution, study one assesses whether people's perceptions of police as a moral, just and appropriate institution-operationalized as normative alignment between police and citizen values (Jackson et al, 2012-are founded primarily in judgements of procedural justice, as has been found in the US (Sunshine & Tyler, 2003;Tyler & Fagan, 2008;White et al, 2016), UK (Jackson et al, 2012, Australia (Murphy & Cherney, 2012;Mazerolle et al, 2013;Bradford et al, 2014a) and indeed Israel (Jonathan-Zamir & Weisburd, 2014;Mentovich et al, 2018), or whether São Paulo residents place greater emphasis on bounded authority (the restrained use of power, which extends beyond procedural justice), distributive justice and effectiveness in the fight against crime. We also assess whether those who see police violence against criminal out-groups as acceptable also view this as a normatively justifiable use of power, above and beyond traditional perceptions of police conduct, i.e.…”
Section: Study One: What Legitimates the Police In São Paulo?mentioning
confidence: 99%
“…The majority of studies using this approach have found that the most important predictor of legitimacy is the extent to which people think that officers act in procedurally just ways. This is the case in the US (Sunshine & Tyler 2003;Reisig et al 2007;White et al 2016), UK (Huq et al 2011;Bradford 2014), Australia (Murphy & Cherney 2012;Murphy et al 2018), Israel (Mentovich et al 2018), China (Sun et al 2017), and in Continental Europe (Hough et al 2013;Dirikx & Ven den Bulck 2013). Notably, however, effectiveness and lawfulness judgements do seem to play a more important role in predicting empirical legitimacy in Pakistan and South Africa (Jackson et al 2014;.…”
Section: The Standard Approach To Studying Empirical Legitimacymentioning
confidence: 99%